Experiencias de trabajo docente: análisis de caso en la Unidad Educativa Antonio de Alcedo del cantón Pangua - Sigcha Yanchaliquin, Mirian Teresa (2016)
That teachers and teachers in his years of work in the classroom with children, build pedagogical knowledge that can be shared with those who are still in training or have little experience in teaching. The present work is to understand the reality addressed teachers and the work done within and outside educational classrooms, considering professional performance in the experience of teaching. Institution teachers are increasingly investigating the pedagogical action oriented one Rebuilding the New School Practices and Experiences Growing encouraging the teaching. Learning Experiences son experienced teachers for their own educational work. Teachers have narrated his own experience that have lived with the students, parents, teachers and community residents inside and outside of the classroom, sin embargo these experiences helps re Looking experiences that have already happened and from Way seta site can be renewed.